The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.4049/jimmunol.181.2.1034
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Regulatory T Cells and Effector T Cell Deletion in Tolerance Induction by Costimulation Blockadel

Abstract: Blocking of costimulatory signals for T cell activation leads to tolerance in several transplantation models, but the underlying mechanisms are incompletely understood. We analyzed the involvement of regulatory T cells (Treg) and deletion of alloreactive cells in the induction and maintenance of tolerance after costimulation blockade in a mouse model of graft-vs-host reaction. Injection of splenocytes from the C57BL/6 parent strain into a sublethally irradiated F1 offspring (C57BL/6 × C3H) induced a GVHR chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 34 publications
(37 reference statements)
5
42
2
Order By: Relevance
“…Our data indeed also show a role for Tregs in the effects of costimulation blockade. It has already been suggested by several groups that Tregs are involved in tolerance induction by costimulation blockade (10,(13)(14)(15). CD40L blockade especially was found to be associated with an enhanced Treg function in previous studies (13-15, 19, 20).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Our data indeed also show a role for Tregs in the effects of costimulation blockade. It has already been suggested by several groups that Tregs are involved in tolerance induction by costimulation blockade (10,(13)(14)(15). CD40L blockade especially was found to be associated with an enhanced Treg function in previous studies (13-15, 19, 20).…”
Section: Discussionmentioning
confidence: 86%
“…We and others have shown that combined blockade of the CD40/ CD40L interaction and the CD28/B7 interaction completely prevents GVHD after allogeneic splenocyte transfer in mice and results in tolerance (8)(9)(10). Separate blockade of these costimulatory pathways is not effective.…”
Section: Mr1 Treatment Prevents Gvhd Induced By Cd4mentioning
confidence: 99%
See 3 more Smart Citations